Avaliação da imunoexpressão de proteínas da via de sinalização Wnt canônica e não canônica no adenocarcinoma gástrico - Oliveira, Levindo Alves de [UNIFESP] (2017)
Objectives: The aim was to analyze the expression of proteins in canonical and non-canonical Wnt signaling pathways in gastric adenocarcinoma tissue. To correlate the expression of such proteins with the patients’ biodemographical characteristics and morphological and anatomopathological characteristics of the tumor. Method: The expression of proteins in Wnt signaling pathways (Wnt-5a, FZD5, GSK3B, axin, CK1, ubiquitin, D1 cyclin and C-MYC) was evaluated in 72 patients who underwent gastric adenocarcinoma surgery. Forty-five (64.3%) were male and the age average was 64.6±11.8 years. The protein level was determined by immunohistochemistry using monoclonal antibodies in gastric tissue samples in tissue microarray. Results: The expression of CK1 protein was positive in cell cytoplasm and significant in tumors without compromised surgical margins (p= 0.031). The ubiquitin protein presented strong expression in both cell nucleus and cytoplasm and was significantly more intense in both nucleus and cytoplasm of cells of moderately and well-differentiated tumors (p= 0.037) and in intestinal tumors (p = 0.031). The D1cyclin protein was expressed only in cell nucleus and was significantly more intense in male patients’ tumors (p= 0.039). The C-MYC protein was expressed in both cell cytoplasm and nucleus and the absence of its cytoplasmic expression was significantly higher in intestinal tumors (p= 0.028) and significant odds ratio (p= 0.021). The immunoexpressions of the Wnt-5a and Frizzled-5 proteins did not present significant differences (p≤0.05) regarding the epidemiological characteristics of the patients and anatomopathological aspects of the tumor. Conclusions:The strong expression of the protein of Wnt signaling pathway suggests the relevance and involvement of the canonical pathway in the occurrence of gastric adenocarcinoma. The significant absence of expression of Wnt-5a and FZD5 proteins suggests that the non-canonical pathway is not activated in gastric adenocarcinoma tissue.